2022
DOI: 10.1364/ol.477155
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of 4096QAM THz MIMO wireless delivery employing one-bit delta-sigma modulation

Abstract: We experimentally demonstrate 2-Gbaud 4096-ary quadrature amplitude modulation (4096QAM) signal transmission over 2-m wireless distance at 370 GHz in a photonics-aided terahertz (THz)-wave communication system. By using one-bit quantized delta-sigma modulation (DSM) and photonics-aided technology, we successfully achieve the transmission of high-order QAM signals over THz multiple-input multiple-output (MIMO) links. After 2 m of free space transmission, its bit error rate (BER) is below the 20% soft-decision f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…6, we can see that the VNLE can bring a sensitivity gain of ∼2.2 dB at the soft-decision forwarderror-correction (FEC) threshold of 1.56 × 10 −2 . Considering the FEC overhead of 15% [19,22] , the net bit rate is 60 × 4 × 2= 1 15% = 417.4 Gbit=s. In addition, we can notice that BER bounces appear in both Figs.…”
Section: Experiments Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6, we can see that the VNLE can bring a sensitivity gain of ∼2.2 dB at the soft-decision forwarderror-correction (FEC) threshold of 1.56 × 10 −2 . Considering the FEC overhead of 15% [19,22] , the net bit rate is 60 × 4 × 2= 1 15% = 417.4 Gbit=s. In addition, we can notice that BER bounces appear in both Figs.…”
Section: Experiments Results and Discussionmentioning
confidence: 99%
“…Table 1 summarizes a series of important achievements that have been successfully achieved regarding the MIMO delivery based on photonics PDM-systems at the THz band [17][18][19][20][21][22][23][24] . For example, Li et al have experimentally demonstrated a photonics-assisted fiber-wireless 2 × 2 MIMO delivery system at the THz-band, which can support 15 Gbit/s net bit rate PDM quadrature-phase-shift-keying (PDM-QPSK) signals delivery [17] .…”
Section: Introductionmentioning
confidence: 99%
“…Higherorder QAM signal transmission requires higher signal-to-noise ratios (SNRs) and higher digital-to-analog converter (DAC) resolution. Recently, in research based on network feedforward, ultrahigh order QAM transmission has been achieved by replacing the traditional common public radio interface (CPRI) with delta-sigma modulation (DSM) technology, improving spectral efficiency [12][13][14][15][16] . DSM technology can convert highorder QAM signals to 1-bit signals for transmission, alleviating some of the problems caused by ultrahigh-order QAM transmission [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in research based on network feedforward, ultrahigh order QAM transmission has been achieved by replacing the traditional common public radio interface (CPRI) with delta-sigma modulation (DSM) technology, improving spectral efficiency [12][13][14][15][16] . DSM technology can convert highorder QAM signals to 1-bit signals for transmission, alleviating some of the problems caused by ultrahigh-order QAM transmission [13][14][15] . The 1-bit quantized signals in QAM transmission are equivalent to quadrature phase shift keying (QPSK) signals, providing a higher SNR tolerance.…”
Section: Introductionmentioning
confidence: 99%